Preliminary Screening of Antibacterial Compounds from Palar River Basin Flora - K. Kavitha, N. Ravichandran, A. Suresh, V. Gopalakrishnan, G. Vijaiyan Siva, G. Suresh, B. Ramesh, (Journal of Phytology, 2010)
Considering the significance of phytochemicals as antimicrobial agents, attempt was made in the present study, to categorize several rare plant species present in and around Palar river basin and to assess their antimicrobial activity. The densities of the green cover of the Palar river basin flora were assessed by the Google Earth software. Totally 28 plants were identified and classified into 17 families according to binomial classification system. Plant extracts were prepared from leaves of all collected plants by using methanol and chloroform. Thus, the crude methanol and chloroform extracts of 28 plant species were subjected to preliminary screening against 6 strains of human bacterial pathogen using the dick diffusion method at 500 Ã‚Âµg/disc concentrations. The results indicated that 21 different plant species exhibited activity against one or more of the bacteria while four species, viz., Ammania baccifera, Plectranthus sp., Vitex trifolia and Vitex negundo showed activity against all test organisms. The plants containing bioactive metabolites demonstrated stronger anti-microbial properties stressing the need for further investigations using fractionated extracts and purified chemical components.